2020
DOI: 10.1108/ijcma-08-2019-0128
|View full text |Cite
|
Sign up to set email alerts
|

Linkages between group level task conflict and individual level outcomes in non-routine technical jobs

Abstract: Purpose This study aims to build on the existing research regarding workplace conflict by arguing that task conflict (TC) leads to resource gains for individuals with non-routine technical jobs, which increases individuals’ work engagement (WE) and leads to positive individual-level outcomes. Specifically, this study uses a resource investment/acquisition approach with the aim of offering insight into the consequences of group-level TC on individual-level outcomes, including task performance (TP), contextual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Pakistan was selected as the empirical context because in Pakistan interpersonal conflict indicates a great threat to organization’s performance (Shaukat et al , 2017). More specifically, Pakistan’s media, information technology (IT) and telecom sectors have grown rapidly, suggesting a need for careful consideration of intra-organizational issues, such as interpersonal conflicts (Yousaf et al , 2020). Moreover, the high demand for services of interrelated sectors of media, IT, and telecom led to intensified competition putting pressure on those who work in these sectors to perform well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pakistan was selected as the empirical context because in Pakistan interpersonal conflict indicates a great threat to organization’s performance (Shaukat et al , 2017). More specifically, Pakistan’s media, information technology (IT) and telecom sectors have grown rapidly, suggesting a need for careful consideration of intra-organizational issues, such as interpersonal conflicts (Yousaf et al , 2020). Moreover, the high demand for services of interrelated sectors of media, IT, and telecom led to intensified competition putting pressure on those who work in these sectors to perform well.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the high demand for services of interrelated sectors of media, IT, and telecom led to intensified competition putting pressure on those who work in these sectors to perform well. In turn, these employees generally face a heavy workload and came across different types of work-related conflict (Yousaf et al , 2020). Furthermore, gender and emotions are particularly important in a developing country like Pakistan, which is predominately a male-oriented society where issues of traditional negative gender-role stereotyping for women, sexual discrimination, domestic violence, fundamentalism and intimidation against women, lower literacy and employment rates for women are still prevalent (see UN report: The World’s Women, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, in the light of AET, it is argued that task and process conflicts, are work events (Yang and Mossholder, 2004) that foster negative emotions among employees facing task or/and process conflicts, which, in turn, will increase relationship conflict. Conflicts arise when two or more social entities interact to achieve their objectives (Rahim, 2011), which gives rise to competitive orientation and creates negative feelings (Zhang et al , 2019). If an individual’s suggestion is continuously shut down during task and process conflicts, they may consider it a personal rejection, which can foster negative emotions (de Wit et al , 2013).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…If an individual’s suggestion is continuously shut down during task and process conflicts, they may consider it a personal rejection, which can foster negative emotions (de Wit et al , 2013). Therefore, task and process conflicts can enhance employees’ negative emotions (Zhang et al , 2019). Moreover, during task conflict, while defending one’s own point of view and disagreeing with the others’ point of views, nonverbal elements such as tone of voice, facial expression and gestures stimulate the emotional response of others (Yang and Mossholder, 2004) and foster negative emotions.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…As we aim to explain individual creativity, we depart from team-level definitions of task conflict (Jehn, 1997) and define task conflict at the individual level as task-related disagreements that an employee has with her or his teammates (Korsgaard et al , 2008; Li et al , 2019). While task conflict has been conceptualized as a team-level construct (Jehn, 1997; Yousaf et al , 2020), more recent research has shown that team members often have a different amount, frequency and perception of task conflict with teammates (De Clercq and Pereira, 2020; De Clercq et al , 2017; Jehn et al , 2010; Li et al , 2019). It is, therefore, important and appropriate to analyze task conflict at the individual level and its effects on individual creativity.…”
mentioning
confidence: 99%